Hubungan Dukungan Orang Tua Dengan Keberhasilan Toilet Training Pada Anak Usia Prasekolah Di TK Pertiwi Sine 1 Sragen - Effendi, Ibnu Hajar, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2016)
Toilet training is one of the stages of child development toddler. But only viewable toilet training was a result of developments at preschool age, because at the age of 3 years and older children can only control the bladder. Toilet training is the first step to exercise independence and stimulate further growth and development. Many factors affect the success of toilet training, one parent support. But in these days, not a few parents were wrong in caring for and guide their children. Such strict rules or loose rules to children. The purpose of this study was to determine the relationship of parental support with successful toilet training to preschoolers at TK Pertiwi Sine 1 Sragen. This research method is descriptive correlation with cross sectional approach. Samples of this study were 32 respondents with a total sampling of the total population. The research instrument for the support of parents and the successful toilet training is given and a questionnaire filled out by the child's parents. Data analysis using Spearman rho test. The results were obtained support from parents on the success of toilet training in preschool children in TK Pertiwi Sine 1 Sragen mostly with good support, as many as 29 respondents (90.63%). The success of toilet training in preschool children in TK Pertiwi Sine 1 Sragen most categories either, as many as 25 respondents (78.1%). The results of Spearman rank correlation (rho) of (+) 0.638 with significant values (p value) = 0.000. Conclusion: there is a strong correlation between the positive directional parental support withsuccessful toilet training in preschool children in TK Pertiwi Sine 1 Sragen. Keywords: parent support, the success of toilet training, preschool